2009
DOI: 10.4067/s0718-19572009000200022
|View full text |Cite
|
Sign up to set email alerts
|

Distribución de merluza (Merluccius hubbsi Marini, 1933) en el Mar Argentino (41°- 48°S) en relación con parámetros oceanográficos durante el invierno (1996-2003)

Abstract: Revista de Biología Marina y Oceanografía 44(2): 497-510, agosto de 2009 Distribución de merluza (Merluccius hubbsi Marini, 1933) en el Mar Argentino (41°-48°S) en relación con parámetros oceanográficos durante el invierno (1996-2003)Distribution of the Argentine hake (Merluccius hubbsi Marini, 1933) in the Argentine Sea (41º-48ºS) in relation to oceanographic parameters during winter (1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003) Abstract.-Salinity and temperature data recorded during 1996-2003 within the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 8 publications
0
10
0
4
Order By: Relevance
“…This could result in males diving at greater depths than females, which could result in a vertical segregation between sexes (Yamamoto et al ) and in males using more offshore areas than females. Hake and argentine squid Ilex argentinus appears to be present closer to the edge of the continental slope or at deeper waters (Brunetti et al , Louge et al ), and anchovy closer to the coast and less deep (Buratti ), matching male and female penguin distribution, respectively. This spatial segregation between sexes was also supported by our description of their isotopic niche (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could result in males diving at greater depths than females, which could result in a vertical segregation between sexes (Yamamoto et al ) and in males using more offshore areas than females. Hake and argentine squid Ilex argentinus appears to be present closer to the edge of the continental slope or at deeper waters (Brunetti et al , Louge et al ), and anchovy closer to the coast and less deep (Buratti ), matching male and female penguin distribution, respectively. This spatial segregation between sexes was also supported by our description of their isotopic niche (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Migration is a strategy adopted by a variety of species, which enables the use of seasonal resources (Newton ). In marine ecosystems, top predators follow fish stocks, dispersing with them (Lehodey et al , Boersma et al , Louge et al ). Some marine bird species differ according to sex in scheduling, destination and latitudinal range during the non‐breeding periods (González Solís et al , Müller et al ), while other species have more overlap in foraging zones between females and males (González Solís et al ).…”
Section: Introductionmentioning
confidence: 99%
“…In our study area a bottom water temperature gradient from north to south of 1.5-2ºC is observed during all seasons. According to Louge et al (2009Louge et al ( , 2011 during wintertime, the mean values of bottom water temperature ranged between 8.5-9.5ºC in 43-45ºS, while in the north and south of San Jorge Gulf they ranged between 8.0-8.5ºC and 7.0-7.5ºC, respectively. In summertime, mean values were between 12.0-15.0ºC in 43-45ºS, and in the gulf they ranged between 11.0-12.0ºC in coastal waters and 8.0-9.0ºC in the inner area.…”
Section: Discussionmentioning
confidence: 99%
“…Of two main stocks, the southern or Patagonian stock (41°–55° S) is the most abundant, accounting for 85% of total hake biomass of the ACS. Age 0+ year M. hubbsi of this stock have their nursery and settlement location in the San Jorge Gulf (SJG; Figure ), where they tend to aggregate in coastal sectors (Álvarez‐Colombo et al ., ), with highest percentages at the south extreme, intermediate values in the central region, drastically diminishing towards the north (Louge et al ., ; Santos et al ., ). It has been suggested that this distribution might respond to certain temperature and salinity ranges as well as to zooplankton prey concentrations (Louge et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Age 0+ year M. hubbsi of this stock have their nursery and settlement location in the San Jorge Gulf (SJG; Figure ), where they tend to aggregate in coastal sectors (Álvarez‐Colombo et al ., ), with highest percentages at the south extreme, intermediate values in the central region, drastically diminishing towards the north (Louge et al ., ; Santos et al ., ). It has been suggested that this distribution might respond to certain temperature and salinity ranges as well as to zooplankton prey concentrations (Louge et al ., ). Pre‐recruits prey mainly upon euphausiids and amphipods during austral summer, although decapods are included in the diet in a lower proportion (Temperoni et al ., ).…”
Section: Introductionmentioning
confidence: 99%